Oxygen-dependent distinct expression of hif-1α gene in aerobic and anaerobic tissues of the Amazon Oscar, Astronotus crassipinnis - Heinrichs-Caldas, Waldir D.; Campos, Derek Felipe de; Paula-Silva, Maria Nazaré N.; Almeida-Val, Vera Maria Fonseca (Comparative Biochemistry and Physiology. Part B: Biochemistry & Molecular Biology, 2019)
The aquatic habitats of the Amazon basin present dramatic variation of oxygen level, and, to survive such changes, many aquatic animals developed biochemical and physiological adaptations. The advanced teleost Astronotus crassipinnis (Perciformes) is a fish tolerant to hypoxia and known to endure such naturally variable environments. Hypoxia-Inducible factor-1α (hif-1α) is among the most important and studied genes related to hypoxia-tolerance, maintaining regular cellular function and controlling anaerobic metabolism. In the present work, we studied hif-1α expression and related it to changes in metabolic pathways of Astronotus crassipinnis exposed to 1, 3 and 5 h of hypoxia, followed by 3 h of recovery. The results show that A. crassipinnis depresses aerobic metabolic under hypoxia, with a decrease in glycolysis and oxidative enzyme activities, and increases its anaerobic metabolism with an increase in LDH activity coupled with a decrease in oxygen consumption, which indicates an increase in anaerobic capacity. In addition, the animal differentially regulates hif-1α gene in each tissue studied, with a positive relationship to its metabolic profile, suggesting that hif-1α might be one of the most important induction factors that regulate hypoxia tolerance in this species. © 2018 Elsevier Inc.
Keywords: Citrate Synthase; Glucose; Hypoxia Inducible Factor 1alpha; Lactate Dehydrogenase; Lactic Acid; Malate Dehydrogenase; Oxidoreductase; Oxygen; Fish Protein; Hypoxia Inducible Factor 1alpha; Lactate Dehydrogenase; Aerobic Metabolism; Anaerobic Capacity; Anaerobic Metabolism; Animals Tissue; Astronotus Crassipinnis; Controlled Study; Enzyme Activity; Female; Gene Expression; Glucose Blood Level; Glycolysis; Hypoxia; Lactate Blood Level; Liver; Male; Nonhuman; Oxygen Concentration; Oxygen Consumption; Perciformes; Priority Journal; Respirometry; Muscle, Skeletal; Adaptation; Animals; Antibody Specificity; Aquaculture; Biological Model; Cell Hypoxia; Cichlid; Classification; Energy Metabolism; Enzymology; Gene Expression Regulation; Genetics; Growth, Development And Aging; Metabolism; Physiology; Randomization; Time Factor; Adaptation, Physiological; Animal; Aquaculture; Cell Hypoxia; Cichlids; Energy Metabolism; Female; Fish Proteins; Gene Expression Regulation, Developmental; Glycolysis; Hypoxia-inducible Factor 1, Alpha Subunit; Lactate Dehydrogenases; Liver; Male; Models, Biological; Muscle, Skeletal; Organ Specificity; Oxygen Consumption; Random Allocation; Time Factors